Targeting microRNA-143 in colorectal cancer: advances in molecular biosciences for biomarker-based diagnostics, therapeutic strategies, and drug resistance prediction - Wang, Xue; Wang, Lei; Ke, Long (Frontiers in Molecular Biosciences, 2025)
Colorectal cancer (CRC) persists as a significant global health challenge, distinguished by intricate molecular modifications and a notable propensity for resistance to standard therapeutic interventions. Among the regulatory factors contributing to CRC pathogenesis, microRNAs (miRNAs) have emerged as pivotal regulators of gene expression, presenting innovative prospects for diagnostic and therapeutic advancements. Notably, microRNA-143 (miR-143) has attracted considerable attention as a tumor-suppressive miRNA, exhibiting diverse functions in the development, progression, and therapeutic response of CRC. This review delineates an exhaustive examination of the molecular mechanisms by which miR-143 modulates critical oncogenic pathways, encompassing KRAS signaling, epithelial-mesenchymal transition, and metabolic reprogramming. We underscore recent progress in the molecular biosciences that position miR-143 as a promising biomarker for the early detection and prognosis of CRC. Furthermore, we investigate its emergent function in the modulation of sensitivity to chemotherapeutic and targeted therapeutic agents, emphasizing its potential utility in predicting and mitigating drug resistance in CRC cells. By synthesizing contemporary findings within the domains of molecular diagnostics and therapeutic interventions, this review accentuates the clinical potential of targeting miR-143 in the personalized management of CRC and the prediction of drug resistance.